A review of entrepreneurship education for college students in China - Mansheng Zhou; Haixia Xu (Administrative Sciences, 2012)
Partly as a result of the rapid growth in Chinese higher education, graduate placement has become a critical issue facing colleges and universties. In response, one of the policy initiatives adopted by the Chinese government is for higher education institutions to put an emphasis on entrepreneurship education. In 2002, the Ministry of Education launched a pilot program on carrying out entrepreneurship education in nine prestigious higher education institutions in China. Since then, many colleges and universities have adopted this innovation in education. This study attempts to examine entrepreneurship education as an innovative solution to the challenges facing higher education in China. It first introduces the background for promoting entrepreneurship education in China, analyzes the entrepreneurship education programs and activities in three selected universities, assesses the state of entrepreneurship education both from a student perspective and also through a comparison with developments in the United States, and concludes with recommendations for further developments in entrepreneurship education in China's colleges and universities.
Keywords: 350; China; entrepreneurship education; higher education; innovation